Karakteristik temperatur fluida dingin pada grooved double pipe heat exchanger - Putu Wijaya Sunu; I Putu Darmawa; Anak Agung Ngurah Bagus Mulawarman; I Made Suarta; I Putu Gede Sopan Rahtika (Jurnal Teknosains, 2020)
Heat exchangers have widespread applications in many industrials process. There are many kind of heat exchanger. One of the simply heat exchanger is double pipe heat exchanger. The need for lightweight and enhancing the heat transfer of heat exchanger accomodated by surface engineering. One of the surface passive technique applications is groove. Incising groove in pipe as concerned wide consideration as it need no additional power, decrease in weight of system and hence give more benefit in heat transfer. The characteristics of heat transfer in grooved double pipe heat exchanger was investigated experimentally in this article. The aim of this investigation is to reveal the phenomenon of temperature characteristics of cold fluid in the heat transfer process in the grooved double pipe heat exchanger. In this study, water are used as both hot and cold fluid with counter flow pattern, and the water flow rate equal to 15 lpm for both fluid. Grooves were incised on the annulus area in the outer wall of tube side with rectangular shape and circumferential pattern. The characteristics of groove dimension that are height of groove is 0,3 mm; distance between grooves is 8 mm; and the groove space which is as independent variables are 1 mm and 2 mm. The data from 1 mm and 2 mm grooves space were compared with no grooved double pipe heat exchanger data (smooth pipe). The hot fluid temperature is 50 ± 0,50C while the cold fluid temperature is 30 ± 0,50C. The temperature data on the inlet and outlet side of heat exchangers for smooth pipe, 1 mm and 2 mm groove space were compared to find out the characteristics of increasing cold fluid temperature. This study used the temperature rate and temperature acceleration method to compare the variables. The result shows that groove installation increases the amount of heat absorbed by cold fluid. The heat exchanger with 1 mm groove spaces, was able to absorb heat about ± 2.3 % better than heat exchanger with 2 mm groove space and 13,1 % better than heat exchanger with no groove.